Diagnosis and Treatment of Chronic Myelomonocytic Leukemias in Adults: Recommendations From the European Hematology Association and the European LeukemiaNet. Issue 6 (December 2018) - Itzykson, Raphael; Fenaux, Pierre; Bowen, David; Cross, Nicholas C.P.; Cortes, Jorge; De Witte, Theo; Germing, Ulrich; Onida, Francesco; Padron, Eric; Platzbecker, Uwe; Santini, Valeria; Sanz, Guillermo F.; et al.
Abstract : Abstract: Chronic myelomonocytic leukemia (CMML) is a disease of the elderly, and by far the most frequent overlap myelodysplastic/myeloproliferative neoplasm in adults. Aside from the chronic monocytosis that remains the cornerstone of its diagnosis, the clinical presentation of CMML includes dysplastic features, cytopenias, excess of blasts, or myeloproliferative features including high white blood cell count or splenomegaly. Prognosis is variable, with several prognostic scoring systems reported in recent years, and treatment is poorly defined, with options ranging from watchful waiting to allogeneic stem cell transplantation, which remains the only curative therapy for CMML. Here, we present on behalf of the European Hematology Association and the European LeukemiaNet, evidence- and consensus-based guidelines, established by an international group of experts, from Europe and the United States, for standardized diagnostic and prognostic procedures and for an appropriate choice of therapeutic interventions in adult patients with CMML.